2021
DOI: 10.3390/jcm10174015
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Liver Transplant Recipients: A Systematic Review

Abstract: Liver transplant (LT) recipients are considered a vulnerable population amidst the COVID-19 pandemic. To date, available data have been heterogeneous and scarce. Therefore, we conducted a systematic literature review identifying English-language articles published in PubMed between November 2019 and 30th May 2021. We aimed to explore three areas: (1) outcome and clinical course; (2) immunological response after COVID-19 in LT recipients; and (3) vaccination response. After systematic selection, 35, 4, and 5 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 79 publications
2
18
0
Order By: Relevance
“…The clinical presentation of COVID-19 in LT recipients does not seem dissimilar to that of patients with non-LT, with respiratory symptoms being the pivotal ones. However, several studies highlighted a higher rate of GI manifestations in this population than in patients with non-LT (30% vs 12%, respectively; p<0.0001),102 with rates of diarrhoea ranging from 22% to 30% among the former 103…”
Section: Covid-19 and Liver Transplantmentioning
confidence: 78%
“…The clinical presentation of COVID-19 in LT recipients does not seem dissimilar to that of patients with non-LT, with respiratory symptoms being the pivotal ones. However, several studies highlighted a higher rate of GI manifestations in this population than in patients with non-LT (30% vs 12%, respectively; p<0.0001),102 with rates of diarrhoea ranging from 22% to 30% among the former 103…”
Section: Covid-19 and Liver Transplantmentioning
confidence: 78%
“…In Campania region (Southern Italy) on the 16th of January 2021 the infection rate of SARS-CoV-2 and its case fatality rate have been of 5.39% and 3.15%, respectively 1 . In this scenario, the liver transplant population represents a priori a vulnerable cohort of patients at increased risk of infections and poor outcome due to chronic immunosuppression, high rates of comorbidities and advanced age 17 , 18 . Whether they are at particularly high risk for critical COVID-19 in real clinical practice still requires further evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The new coronavirus pathogen, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has been identified as the cause of coronavirus disease 2019 (COVID-19) 1 . Preliminary reports indicated that in liver transplant (LT) recipients, the clinical outcome following COVID-19 was better compared to other solid organ transplant recipients 2 and not per se worse compared to the general population 3 . However, more recent reports indicate that mortality in LT recipients remains particularly elevated 4,5 .…”
Section: Introductionmentioning
confidence: 99%